2018
DOI: 10.1071/wr17106
|View full text |Cite
|
Sign up to set email alerts
|

Northward bound: the distribution of white-tailed deer in Ontario under a changing climate

Abstract: Context Global climatic changes are increasingly producing observable shifts in species distributions. It is widely believed that the northern distribution of white-tailed deer (Odocoileus virginianus) in North America is limited by cold winter temperatures and deep snow. Under all climate change scenarios, it is likely that the adverse effects of winter will diminish, which may result in a northward expansion of the distribution of white-tailed deer. Aims The goal of this project was to quantify the drivers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 28 publications
8
34
0
Order By: Relevance
“…The influence of winter weather on white‐tailed deer winter mortality risk which we observed is consistent with other studies of deer survival in northern climates (e.g., Delgiudice et al, ; Dumont et al, ; Nelson & Mech, ), and generally supports the hypothesis that winter weather conditions are the primary factor limiting the northern distribution of white‐tailed deer in North America (Dawe, Bayne, & Boutin, ; Kennedy‐Slaney, Bowman, Walpole, & Pond, ). Our results indicated that the most critical period of winter deer mortality risk is late winter–early spring (April and May) when snowmelt occurs, but mortality risk varied widely among years depending on weather conditions.…”
Section: Discussionsupporting
confidence: 92%
“…The influence of winter weather on white‐tailed deer winter mortality risk which we observed is consistent with other studies of deer survival in northern climates (e.g., Delgiudice et al, ; Dumont et al, ; Nelson & Mech, ), and generally supports the hypothesis that winter weather conditions are the primary factor limiting the northern distribution of white‐tailed deer in North America (Dawe, Bayne, & Boutin, ; Kennedy‐Slaney, Bowman, Walpole, & Pond, ). Our results indicated that the most critical period of winter deer mortality risk is late winter–early spring (April and May) when snowmelt occurs, but mortality risk varied widely among years depending on weather conditions.…”
Section: Discussionsupporting
confidence: 92%
“…In addition to being superior competitors, southern flying squirrels are carriers of an intestinal parasite that is deadly to northern flying squirrels 63,64 . In the same forests, white-tailed deer and their associated parasites are expanding northward in response to climate change 65 . Due to the introduction of these parasites as well as increasing thermal stress, moose, boreal specialists, are ultimately predicted to be extirpated from sites along their southern range edge 66 .…”
Section: Impacts Of Range Shifting Can Parallel Introductionsmentioning
confidence: 99%
“…Verme (); Karns (); Nelson and Mech (); Mech et al (); Messier (); DelGiudice (); Post and Stenseth (); Patterson and Messier (, ); DelGiudice et al (, , ); Kunkel et al (); Garroway and Broders (); Millington et al (); Simard et al (); Dawe et al (); Notaro et al (); Giroux et al (); Kennedy‐Slaney et al ().…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, Dawe et al () reported that climate, measured by an index of winter severity, was the most important variable in determining white‐tailed deer distribution in boreal Alberta, Canada. Kennedy‐Slaney et al () reported that land cover and temperature or snow depth were included in the best models of deer occupancy in Ontario, Canada. They ran the model with variables derived from several climate change scenarios, and the authors concluded that deer have a high probability of expanding their range in Ontario over the 21st century (Kennedy‐Slaney et al ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation